Short report: Follow‐up of Bahamian women with a BRCA1 or BRCA2 mutation. Issue 2 (20th December 2017) - Narod, Steven A.; Butler, Raleigh; Bobrowski, David; Akbari, Mohammad R.; Curling, DuVaughan; Lunn, John; Ho, Catherine; Panahi, Sara; Llacuachaqui, Marcia; Donenberg, Talia; Hurley, Judith
Abstract: Purpose: We sought to determine to what extent the knowledge of carrying a BRCA1 or BRCA2 mutation influences the uptake of preventive surgeries in Bahamian women, including bilateral salpingo‐oophorectomy and bilateral mastectomy. Patients and methods: The study population consisted of 78 female residents of the Bahamas for whom a BRCA1 or BRCA2 mutation had been detected between 2004 and 2014. The mean age of the 78 participants at the time of genetic testing was 46 years (age range 22–73 years). The mean time of follow‐up was 4.4 years. Results: Of the 78 study participants, 19 women had a bilateral salpingo‐oophorectomy (24%). Seven out of 37 patients who had unilateral breast cancer chose to remove the unaffected contralateral breast (19%). Three of 13 patients with no history of breast cancer chose to have a prophylactic bilateral mastectomy (23%). Conclusion: Preventive surgery is an acceptable option for a significant proportion of Bahamian women with a BRCA1 or BRCA2 mutation. It will be important to identify and reduce barriers to preventive surgery in the Bahamas in order that the benefit of getting testing can be fully realized. Abstract : We sought to determine to what extent the knowledge of carrying a BRCA1 or BRCA2 mutation influences the uptake of preventive surgeries in Bahamian women. Of the 78 mutation carriers, 19 women had a bilateral salpingo‐oophorectomy (24%). Seven out of 37 patients who had unilateral breast cancer chose to remove the unaffected contralateral breast (19%) and three of 13 patients with no history of breast cancer chose to have a prophylactic bilateral mastectomy (23%).